Development and Validation of an Automotive Axle Power Loss Model. Issue 4 (3rd July 2016) - Talbot, D.; Kahraman, A.; Li, S.; Singh, A.; Xu, H.
ABSTRACT: This study proposes a methodology to predict power losses of automotive axle units, including both load-dependent (mechanical) and load-independent (spin) loss components. This methodology combines a mechanical hypoid gear mesh power loss model, a new tapered roller bearing mechanical power loss model, a gear drag loss model, and empirical viscous bearing power loss formulae to determine the total power loss of an axle unit. The proposed methodology captures the effects of operating conditions (speed and torque and oil temperature and level), contact surface roughness amplitudes, as well as bearing preload on power loss. The model is employed to simulate published axle efficiency experiments. Direct comparisons between measured and predicted power losses are presented to demonstrate the accuracy of the proposed modeling methodology.